Le guerrier, le chat, l'aigle, le poisson et la colonne : la voie spiralée des signes : approche sémilogique, structurale et archéologique du disque de Phaistos - Collet, Serge (Praehistorica Mediterranean, 2017)
The Phaistos Disc is one of the most studied documents of the Minoan civilization, enticing scholars and simple enthusiasts with the mysterious aura that envelops it and with its singularity among Minoan scriptures. It has entered the collective imagination, both at academic and popular levels. Representations of the Disc can be found abundantly in popular culture, from appearances in Mickey Mouse comics to a prop amidst the curios on the tables of a television magician. It is this very overexposure that risks undermining the understanding of an object that is, first and foremost, an archaeological artefact found in a chronological and cultural context. Much has been said and much and has been written about the Disc. Collet brings a new approach.